Sharing the risk at expense of power : Paying wages in equity to face the COVID-19 - Aubert, Nicolas (2020)
This paper aims to discuss which basic implications firms need to be aware of if they decide to include equity shares as a part of salary payments in order for them to tackle financial risks due to the COVID-19 crisis, benefiting with better liquidity. We discuss this alternative from the strand of potential financial benefits, but also include a power perspective, emphasizing how firms could share with employees their decision-making processes as well as a part of their position of traditional hegemony. We concluded that firms’ decision regarding this financial alternative fits into a short-term benefit and at the same time threats a long run position of power.